2015
DOI: 10.1371/journal.pone.0118139
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid Insecticide Residues in Surface Water and Soil Associated with Commercial Maize (Corn) Fields in Southwestern Ontario

Abstract: Neonicotinoid insecticides have come under scrutiny for their potential unintended effects on non-target organisms, particularly pollinators in agro-ecosystems. As part of a larger study of neonicotinoid residues associated with maize (corn) production, 76 water samples within or around the perimeter of 18 commercial maize fields and neighbouring apiaries were collected in 5 maize-producing counties of southwestern Ontario. Residues of clothianidin (mean = 2.28, max. = 43.60 ng/mL) and thiamethoxam (mean = 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 203 publications
(158 citation statements)
references
References 64 publications
10
144
2
2
Order By: Relevance
“…At the highest concentration of clothianidin (0.2 ppm), crayfish were 70% less responsive compared to the control. For both species, we observed behavioral effects at 0.05 ppm, which is within the range of concentrations detected in water samples taken from agricultural areas [42]. Collectively, these results demonstrate that clothianidin can have sublethal effects on the behavior of aquatic invertebrates, at environmentally relevant concentrations, and provide the basis for future work that investigates potentially important sublethal behavioral effects.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…At the highest concentration of clothianidin (0.2 ppm), crayfish were 70% less responsive compared to the control. For both species, we observed behavioral effects at 0.05 ppm, which is within the range of concentrations detected in water samples taken from agricultural areas [42]. Collectively, these results demonstrate that clothianidin can have sublethal effects on the behavior of aquatic invertebrates, at environmentally relevant concentrations, and provide the basis for future work that investigates potentially important sublethal behavioral effects.…”
Section: Discussionsupporting
confidence: 63%
“…The current U.S. EPA Aquatic Life Benchmark for clothianidin (acute exposure) and freshwater invertebrates is 0.011 ppm. Yet, clothianidin has been detected in field samples as high as 0.043 ppm [42]. Given that the sensitivity of G .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The footslope soil concentrations in the control sites are similar to those reported previously (De Perre et al, 2015;Schaafsma et al, 2015;Xu et al, 2016); concentrations of neonicotinoids ranged from 4 to 18 ng/g within fields with multiple years of planting with treated seeds.…”
Section: Soilsupporting
confidence: 84%
“…Mean concentrations in this study were generally lower than those previously measured in surface water runoff from crop fields. Schaafsma et al (2015) reported means of 1000 to 2000 ng/L for CLO and THX in Ontario, while De Perre et al (2015) reported means of ND to 850 ng/L for CLO. These previous studies were conducted in fields with on-going used of coated seeds and would be expected to have higher concentrations than all sites described in this report.…”
Section: Surface Runoff Watermentioning
confidence: 99%